Usulan Perancangan Ulang Tata Letak Lantai Produksi untuk Memaksimalkan Area Produksi (Studi Kasus PT. XYZ) - Nicholas, Rio Wirawan; Hidayat, Trifenaus Prabu; Sugioko, Andre (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2018)
PT. XYZ is a manufacturing company which produced a variety of products with uncertain demand. All of the products made of Polyurethane. This company plans to expand their production floor at the 1st floor to accommodate the machines at the 2nd floor. The reason for this expansion was because the operators have to go to the 2nd floor if they want to produce some small-sized products, which increases the material flow on the production floor. Furthermore, the ovens located only at the first floor, causing the flow to increase even more. If all the machines are at the same floor, the material flow will decrease. The purpose of this research is to propose layout design, which can reduce the distance between machines. This research using quantitative and qualitative approach. Quantitative approach uses ABSMODEL 3 algorithm, while qualitative approach uses CORELAP method. This final proposal also considers some other areas, which is Quality Control and finishing area including racks for finished products. These two approaches compared in order to know which one generates the shortest distance, where the better result turned out the one using quantitative approach with the total distance of 80,67 m.